PENERAPAN DIVERSI DALAM SISTEM PERADILAN PIDANA ANAK: STUDI KASUS DI PENGADILAN NEGERI TANGERANG - Lengkong, Lonna Yohanes; Januar, Inri; Ginting, Jasper Keladius (Fakultas Hukum Universitas Kristen Indonesia, 2024)
This article analyzes the criminal law policy of diversion in the juvenile criminal justice system. The purpose of this article is to find out where diversion is regulated and analyze whether diversion meets the principles of justice for perpetrators and victims of criminal acts. The findings prove that regarding the regulation of diversion criminal law policies in the juvenile criminal justice system that there is a difference in regulation between Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Supreme Court Regulation Number 4 of 2014 concerning Guidelines for the Implementation of Diversion in the Juvenile Criminal Justice System regarding the threat of imprisonment which is a condition for the imposition of diversion on children and the age limit of children is further expanded within PERMA where children who have been married but are not yet 18 (eighteen) are still included in the category of children